The effects of a school-based neurodiversity literacy program for knowledge, attitude, and behavioral intention among adolescents: a pilot single-arm trial - Liow, Jia Li; Pet, Jia Yi; Wong, Xio Zen (2019)
In mainstream schools, there is a lack of understanding, empathy, social acceptance, and awareness in the issue of discriminatory behaviour among the mainstream students and teachers towards the neurodiverse students. Thus, the present study used a mix methods single-arm trial to examine the effects of a neurodiversity literacy program among Malaysian adolescents’ knowledge, attitude, and behavioral intention towards neurodiverse students. Thirty-six high school students aged between 13 and 17 with a mean age of 15 (SD = 1.3) from Penang were recruited as the participants in this study through purposive sampling method. Measures of knowledge, attitude, and behavioral intention were administered to all participants at pre-test and post-test. An open-ended qualitative feedback was also collected from the participants. The quantitative results of the current study indicated that there was a significant increase in knowledge, sheltering subscale of Community Living Attitudes Scale-Intellectual Disability (CLAS-ID) and behavioral intention at post-test, whereas there was no significant difference in empowerment, exclusion, and similarity subscales of CLAS-ID. The qualitative results indicated an increase in the majority of the adolescents’ knowledge, and an improvement in the minority of the adolescents’ attitudes and behavioral intentions. Further research is required to identify the potential impact of a longer duration of a neurodiversity literacy program on the knowledge, attitudes, and behavioral intention of adolescents in Malaysia.